A Comparison of Multiple Constituency Models of Organizational Effectiveness - Zammuto, Raymond F. (Academy of Management Review, 1984)
Four sets of multiple constituency models of organizational effectiveness, which employ relativistic, power, social justice, and evolutionary perspectives, are reviewed. Comparison of these perspectives shows that the construct of organizational effectiveness is both value-based and time-specific. The implications of these findings are examined in the form of potential directions for research on organizational effectiveness.